EU joint purchasing of gas: An assessment - Alex Barnes (The Oxford Institute for Energy Studies, 2023)
In the wake of the gas crisis, in March 2022 the European Council called on the Council and the Commission to examine how 'an aggregator model / single buyer' could help reduce gas prices. The Council also said that Member States and the Commission would 'work together on voluntary common purchase of gas, LNG and hydrogen, making optimal use of the collective political and market weight of the European Union and its Member States to dampen prices in negotiations.' The latter initiative led to the setting up of the EU Energy Platform in April 2022. Further price rises in August 2022 led to the adoption of 'Council Regulation (EU) 2022/2576 enhancing solidarity through better coordination of gas purchases, reliable price benchmarks and exchanges of gas across borders setting up a demand aggregation mechanism' in December 2022. The Regulation sets up temporary rules to set up a service to enable demand aggregation and joint purchasing of gas. It enables the establishment of a 'Temporary service contract' with a service provider to organise demand aggregation and joint purchasing. The service provider aggregates demand of natural gas companies in the EU and seek offers from gas suppliers or producers to match the aggregated demand. All EU gas companies or companies which use gas can participate in the demand aggregation and joint purchasing. Companies which participate in the demand aggregation organised by the service provider may jointly purchase gas but must comply with EU competition law. The regulation itself is only valid for one year although the Commission can propose to extend it based on a review it must conduct by 1st October 2023. It is too early to tell if joint purchasing of gas has been a success due to a lack of information on any gas contacted following matching on the platform. Therefore, it is not possible to tell if buyers have achieved lower prices than they would have done using existing market mechanisms. AggregateEU has succeeded in its limited aim of matching buyers and sellers, and a significant number of market participants have signed up. It is difficult to see how AggregateEU can add much value as the current market framework already enables effective demand aggregation and allows companies which are based in landlocked countries or have limited experience of LNG contracting to access LNG supplies to replace Russian gas flows. Only 20% of the supply matched in the first tender round relates to LNG. This is less than current LNG's current market share of supply to the EU. As currently constructed AggregateEU can only have limited impact on the workings of the gas market as it is only a matching service. There is no obligation for joint purchasing of gas if matching occurs on the platform. It is also only a temporary measure (so far) to address the current gas crisis. It uses the existing gas market architecture and does not give companies any exemption from competition rules, so works within the existing regulatory and market framework. AggregateEU can therefore be seen as complementary to the other means of demand aggregation and matching such as the existing traded markets, even if it is not immediately clear what added benefits it brings. However, there are signs that some in the Commission wish to make the mechanism permanent and extend it. The risk for the natural gas market is that a 'beefed up' mechanism would be detrimental, for example by harming competition between suppliers within the EU. The current liberalised market has worked well - benefitting from competition between LNG and pipeline gas prior to the gas crises, and after the crises quickly attracting LNG supply to replace Russian gas and reducing demand in response to price signals to ensure the market balanced physically. Whilst the added value of the AggregateEU platform is not clear, it has the merit that it is limited in scope and duration and therefore unable to materially harm the internal gas market. This would no longer be the case if, for example, the EU decided to make it more than a matching platform for natural gas, or to require some form of mandatory single buyer. The Commission would need more substantial justification for any upgraded mechanism than that provided for the current arrangements, which are open to question.
Keywords: 330; AggrgeateEU; EU; Europe; Gas; Joint Gas Purchasing; LNG